Simulation of the influence of Lode parameter on ductile fracture using an ellipsoidal void model. (15th October 2021) - Komori, Kazutake
Graphical abstract: Highlights: Influence of Lode parameter μ on fracture strain is calculated and demonstrated theoretically. Fracture strain calculated using ellipsoidal void model for μ = ± 1 is larger than that for μ = 0 . Calculated void shape and void configuration at fracture scarcely depend on μ . Theoretical equivalent strain at fracture for μ = ± 1 is 2 / 3 times larger than that for μ = 0 . Theoretical equivalent strain at fracture almost agrees with that of the calculated. Abstract: The influence of the Lode parameter μ on ductile fracture is simulated using an ellipsoidal void model proposed previously by the author, and is analyzed using an elementary theory proposed in this study. The equivalent strain at fracture calculated using the ellipsoidal void model in the case of μ = + 1 is almost identical to that in the case of μ = - 1 . The equivalent strain at fracture calculated using the ellipsoidal void model in the case of μ = ± 1 is larger than that in the case of μ = 0 . The void shape and the void configuration at fracture calculated using the ellipsoidal void model significantly depend on the stress triaxiality but scarcely depend on the Lode parameter. The proposed elementary theory indicates that the equivalent strain at fracture in the case of μ = ± 1 is 2 / 3 times larger than that in the case of μ = 0 . The equivalent strain at fracture analyzed using the elementary theory almost agrees with that calculated using the ellipsoidal void model.